Patterns of kidney dysfunction in acute‐on‐chronic liver failure: Relationship with kidney and patients' outcome. Issue 8 (10th May 2022) - Napoleone, Laura; Solé, Cristina; Juanola, Adrià; Ma, Ann T.; Carol, Marta; Pérez‐Guasch, Martina; Rubio, Ana‐Belén; Cervera, Marta; Avitabile, Emma; Bassegoda, Octavi; Gratacós‐Ginès, Jordi; Morales‐Ruiz, Manuel; et al.
Abstract: Impairment of kidney function is common in acute‐on‐chronic liver failure (ACLF). Patterns of kidney dysfunction and their impact on kidney and patient outcomes are ill‐defined. Aims of the current study were to investigate patterns of kidney dysfunction and their impact on kidney and patient outcomes in patients with acute decompensation (AD) of cirrhosis, with or without ACLF. This prospective study includes 639 admissions for AD (232 with ACLF; 407 without) in 518 patients. Data were collected at admission and during hospitalization, and patients were followed up for 3 months. Urine samples were analyzed for kidney biomarkers. Most patients with ACLF (92%) had associated acute kidney injury (AKI), in most cases without previous chronic kidney disease (CKD), whereas some had AKI‐on‐CKD (70% and 22%, respectively). Prevalence of AKI in patients without ACLF was 35% ( p < 0.001 vs. ACLF). Frequency of CKD alone was low and similar in both groups (4% and 3%, respectively); only a few patients with ACLF (4%) had no kidney dysfunction. AKI in ACLF was associated with poor kidney and patient outcomes compared with no ACLF (AKI resolution: 54% vs. 89%; 3‐month survival: 51% vs. 86%, respectively; p < 0.001 for both). Independent predictive factors of 3‐month survival were Model for End‐Stage Liver Disease–Sodium score, ACLF status, and urine neutrophil gelatinase–associated lipocalin (NGAL). AKI is almost universal in patients with ACLF, sometimes associated with CKD, whereas CKD alone is uncommon. Prognosis of AKI depends on ACLF status. AKI without ACLF has good prognosis. Best predictors of 3‐month survival are MELD‐Na, ACLF status, and urine NGAL. Abstract : Impairment of kidney function is common in acute‐on‐chronic liver failure (ACLF) but patterns of kidney dysfunction and their impact on kidney and patient outcomes are ill‐defined. Aims of current study were to investigate patterns of kidney dysfunction and their impact on kidney and patient outcomes in patients with acute decompensation (AD) of cirrhosis, with or without ACLF. The results of this study show that AKI (acute kidney injury) is almost universal in patients with ACLF, sometimes associated with CKD, while CKD alone is uncommon and that prognosis of AKI depends on ACLF status.image